The dance of connection : how to talk to someone when you're mad, hurt, scared, frustrated, insulted, betrayed, or desperate - Lerner, Harriet Goldhor (New York : Quill, 2002)
Reveals how to communicate effectively using "voice lessons," enabling readers to convey clearer meanings and strengthen positive emotions and integrity in the face of adversity.
Acknowledgments -- Prologue : Back to the sandbox -- ch.1. Finding your voice -- ch. 2.Voice lessons from my father -- ch.3. Our first family : where we learned (not) to speak -- ch. 4.Should you share vulnerability? -- ch. 5.In praise of pretending -- ch.6. Putting our parents in the hot seat -- ch. 7.Love can make you stupid -- ch. 8.Marriage : where's your bottom line? -- ch.9. "I can't live with this!" Voicing the ultimate in marriage -- ch.10. Warming things up -- ch. 11.Silent men/angry women -- ch.12. Criticism is hard to take -- ch. 13.An apology? Don't hold your breath -- ch. 14.Complaining and negativity : when you can't listen another minute -- ch. 15.The sounds of silence : finding a voice when you're rejected and cut off -- Epilogue : To thine own self be true -- Notes -- Index.
Includes bibliographical references and index.
Keywords: Interpersonal communication; Intimacy (Psychology)